ANTIBIOTIC PROPHYLAXIS IN UROLOGIC PROCEDURE : A COMPREHENSIVE SYSTEMATIC REVIEW - Amal Ramadhani, Rizkia; Fithri Rofifa, Amira (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: Antibiotics are synthetic molecules that can destroy or inhibit the growth of microorganisms without harming the host. They can be used for prophylactic purposes to reduce the incidence of postoperative infection of which duration should not exceed 24hrs in many procedures given one hour prior to incision. Also antibiotics for treatment purposes are given when an established infection has been identified. Urologists commonly prescribe antimicrobial agents before, during, and after urologic procedures. The aim: This study aims to show about antibiotic prophylaxis in urologic procedure. Methods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. So, the experts were able to make sure that the study was as up-to-date as it was possible to be. For this search approach, publications that came out between 2014 and 2024 were taken into account. Several different online reference sources, like Pubmed and SagePub, were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: In the PubMed database, the results of our search brought up 34 articles, whereas the results of our search on SagePub brought up 77 articles. The results of the search conducted for the last year of 2014 yielded a total 26 articles for PubMed and 55 articles for SagePub. The result from title screening, a total 16 articles for PubMed and 25 articles for SagePub. In the end, we compiled a total of 10 papers. We included five research that met the criteria. Conclusion: Antibiotic therapy should be considered only for procedures in which studies have shown a clinical benefit in the prevention of infection. It is important to establish the duration and type of treatment for antimicrobial therapy for surgical prophylaxis in patients with AB who are going to receive urological invasive procedures.